New industrial state - Galbraith, John Kenneth (Deutsch LondonGB, 1972)
Analyses how the modern organisation man identifies his goals with those of the organisation and examines it's implications. Concludes that this has caused a threat to the quality of life, the loss of personality and the uneven development of the economy.